Питання однозначності у викладенні кримінальних процесуальних вимог щодо підготовки й проведення негласних (розшукових) дій - Колесник, В.; Kolesnyk, V. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Розглянуті окремі проблеми, що стосуються нормативного викладення положень кримінального процесуального закону та відомчих нормативних документів, якими встановлено порядок підготовки й проведення негласних слідчих (розшукових) дій. Звертається увага на потребу правильного визначення суб’єкта прийняття рішення про проведення слідчих (розшукових) дій та осіб, яким надано право на їх проведення, Висвітлено окремі проблемні аспекти проведення таких негласних процесуальних дій уповноваженим оперативним підрозділом та складання й направлення прокурору протоколу з результатами їх проведення. The article highlights some problems concerning normative interpretation of the criminal procedural law concepts and departmental normative documents, which determine the procedure/order of preparation and conducting of secret investigative (search) actions. The study places importance on the need to determine precisely the official (Subject) entitled the powers to work out the strategy of the investigation (search) actions and the persons granted the right to carry them out. The author of the article argues that the investigative judge has the right to grant permission, but not to make the decision to hold such secret proceedings. The article sheds light on some problematic aspects of these secret proceedings performed by authorized operating units and the issues of drafting the protocol about the results of the investigation and reporting it to the prosecutor. The institute of secret investigative (detective) actions is an important and effective means of gathering evidence by the prosecution. The norms governing the activities of the investigator, and those of the prosecutor and operational units should be clear, accurate and unambiguous in wording, taking into account that a large number of procedural actions conducted by this institute admit/imply the possibility of a temporary restriction of the individual’s constitutional rights. The persons, whose constitutional rights and interests were temporarily restricted in connection with the secret proceedings, must be informed of such facts timely and in writing by the prosecutor himself or at his request by the investigator in the form established for this purpose.
Issues of Unambiguous Presentation of the Criminal Procedural Requirements Regarding Preparation and Carrying Out Secret Investigation (Search) Actions
Keywords: досудове розслідування; негласні слідчі (розшукові) дії; процесуальні норми; слідчий суддя; слідчий; прокурор; pre-trial investigation; secret investigative (search) actions; procedural norms; investigator; prosecutor; investigative judge; 343.982